Synthesis of Epibatidine Analogues by Pyrrole Diels–Alder Reactions: Rapid Access to Azabicyclo[2.2.1]heptane and 3, 8‐Diazabicyclo[3.2.1]octane Scaffolds for Library Synthesis. Issue 1 (19th December 2016) - Murray, Alexander T.; Packard, Emma; Nortcliffe, Andrew; Lewis, William; Hamza, Daniel; Jones, Geraint; Moody, Christopher J.
Abstract : Analogues of the nicotinic acetylcholine antagonist epibatidine, suitable for diversification, were synthesized by application of a pyrrole Diels–Alder strategy, allowing rapid generation of azabicyclo[2.2.1]heptane bicyclic cores. Further molecular complexity could be accessed by using intramolecular Diels–Alder reactions, or ring expansion by ozonolysis–reductive amination chemistry. Scaffolds were designed such that they could be orthogonally deprotected, yielding three points of diversity for library synthesis, exemplified by 24 compounds synthesized from four cores. Abstract : Efficient access to sp 3 ‐rich bicyclic amines by using pyrrole Diels–Alder reactions translates to novel scaffolds for library synthesis in the European Lead Factory.